2021
DOI: 10.1177/08902070211040978
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Links Between Self-Esteem and the Importance of Self-Direction Values During Adolescence

Abstract: Self-direction values (e.g., independence, curiosity) are among the most important values to people worldwide. However, it is not clear what encourages their development. We propose that self-esteem may be associated with the development of self-direction values because feelings of self-worth provide the confidence needed for independent pursuit. As both independence and self-esteem develop during adolescence, we examined longitudinal associations between self-direction values and self-esteem in adolescents. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…In addition, in line with previous contributions, the stability of difficulties in investments and goals also seems to emerge as a specificity of this developmental stage. This finding seems interesting and could be related to greater difficulty in self‐direction‐related aspects during this developmental stage (Daniel et al, 2021; Sharp, 2020). Finally, the stability of difficulties in relationships with family members is also in line with the literature: conflict within the family plays a central role as a relational training ground during this developmental stage.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, in line with previous contributions, the stability of difficulties in investments and goals also seems to emerge as a specificity of this developmental stage. This finding seems interesting and could be related to greater difficulty in self‐direction‐related aspects during this developmental stage (Daniel et al, 2021; Sharp, 2020). Finally, the stability of difficulties in relationships with family members is also in line with the literature: conflict within the family plays a central role as a relational training ground during this developmental stage.…”
Section: Discussionmentioning
confidence: 87%
“…While we cannot provide definitive explanations for the differences between our results and those of previous studies, our findings of an increasing trend in openness to change values as adolescents grow up may be understood in light of the substantial changes in self-esteem that occur during adolescence (Orth et al, 2018). As suggested by Daniel et al (2021), the growing feelings of competence and mastery associated with self-esteem, which increase during middle adolescence (Orth et al, 2018), could encourage the self-confidence required to set independent goals and pursue risk-taking and independence.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a limited number of studies have investigated these associations during adolescence. For instance, Daniel et al (2021) found that the increase in the importance assigned to self-direction value over time was related to the increase, during adolescence, in both independence and self-esteem. Many studies in the literature on values development have focused on the relationships between values and social environment, such as family (e.g., Barni et al, 2011), school (Berson & Oreg, 2016), and peers (e.g., Daniel et al, 2016).…”
Section: Do Family and Community Factors Influence Personal Values?mentioning
confidence: 99%
“…This is a detriment not only for the children unable to self-direct but also for the adults who are kept from their personal self-direction (Hepburn 2020; Mone and Benga 2022)important in producing parental burnout in democratic countries-negatively affecting their mental health (Roskam et al 2023). Therefore, with self-direction the aim, finding ways and means to permit greater self-direction in children will aid not only children but also their parents/caretakers who then would have time released from supervising children to self-direct their own lives, longitudinally representing both an individual and social benefit (Daniel et al 2023).…”
Section: Introductionmentioning
confidence: 99%